Overfill Resolution Through Non-Surgical Endodontic Treatment: A Case Report - Czopik, Barbara (Iranian Endodontic Journal, 2025)
Continuous improvement and technological progress in the field of microscopic endodontics enable a gradual increase in indications for non-surgical root canal treatment. While most publications report successful surgical management of overfill or extruded foreign bodies into the periapical area, very few report that this complication can be successfully managed with non-surgical endodontic treatment. This case report presents successful management of a lower left second molar (tooth #37) diagnosed with exacerbated chronic apical periodontitis and massive overfill in a 36-year-old patient WITH non-surgical endodontic treatment AND bent H-file to remove extruded material under dental operating microscope control. It discusses technical aspects of this procedure, as well as its possible complications, including a sodium hypochlorite accident.